First Report of Leaf Spot Disease on Rhizophora mucronata from Mangunharjo Village, Semarang City, Central Java, Indonesia - Sibero Mada Triandala; Wulandari Nilam F.; Windarto Seto; Wijaya Yusuf J. (BIO Web of Conferences)
Mangrove diseases are the most neglected threats that might occur in Indonesia’s mangrove ecosystems. During a field study at Mangunharjo village, Semarang City, Central Java, Indonesia, some pests and diseases were found in Rhizophora mucronata, including leaf spot diseases commonly caused by fungi. This study aimed to isolate, determine, and identify the causative agent of leaf spot diseases. Isolation of the causative agent was done using the surface sterilization method, then all isolates were tested for pathogenicity using detached leaf assay on healthy leaves. Furthermore, morphological and molecular identification based on ITS rRNA gene sequence was done to confirm the species of the causative agent. Three endosymbiont fungal strains were isolated from R. mucronata’s leaves with leaf spot disease symptoms. The pathogenicity test confirmed that strain RM1 was the causative agent. The ITS rRNA gene sequence data of strain RM1 had 99.98% similarity to Pestalotiopsis rhizophorae.